Development of Video Tracker-Assisted E-Modules on Parabolic Motion Materials to Train Students Critical Thinking - iswara, Dimas lingga; Risdianto, Eko; Purwanto, Andik (Kasuari: Physics Education Journal (KPEJ), 2022)
This study aims to develop a video tracker-assisted e-module on parabolic motion material to train students' critical thinking in 3 high schools in Bengkulu city. This study used R&D with the ADDIE model according to Dick and Carry. The instruments used were observation, interviews and needs analysis questionnaires which obtained an average result of 84.27% with the category strongly agreeing with the development of e-modules. The e-module learning media will be developed according to the design that has been prepared. The instrument used is a validation sheet consisting of 5 aspects according to BNSP, namely the feasibility of content, language, presentation of material, graphing and critical thinking which gets an average percentage of 89.81% with categories very worthy of use. The student perception sheet has 3 aspects, namely the appearance, presentation of the material and benefits which have an average yield of 82.58% which can be categorized as very good for use. So it can be concluded that the development of e-module learning media assisted by video trackers on parabolic motion materials to train students' critical thinking can be used as a learning medium.